Baseball : how to play the game - Williams, Pete, 1969-; Major League Baseball (Organization) (New York, NY : Universe Pub., 2011)
Overview: Major League Baseball has compiled the definitive instruction manual on learning to play the game. Fully illustrated with action photos of MLB stars illustrating key points and drills for each defensive position, this book also includes special tips from MLB players on batting, base running, the rules of the game, and coaching. Easy-to-follow instructions and diagrams of all the skills beginning players need to master the game--how to throw, hit, and field all the positions--while also promoting good sportsmanship. Each skill and position is presented separately, with photographs and drawings of a player executing the specific skill, advice on how to perform it, and when to use it, and the most common mistakes. Written and compiled by the best baseball instructors, coaches, and players in the world, this comprehensive how-to is informative enough to help even the brightest young stars shine brighter. With keen insights from instruction and developmental coaches, the need to create a positive environment in practice and encourage creativity as well as technical correctness is stressed. Most importantly, the coaches understand that kids are not just small adults--and they back up their understanding with advice on how to help kids fall in love with "America's pastime. " Model training sections construct excellent practice sessions--from warm-up through cool-down exercises and hundreds of drills and games to reinforce--this is an essential tool for all coaches as a guide to improving performance and enjoyment of practice and playing the game. This must-have resource covers it all: Batting, Pitching, Base running and sliding, Specific drills for playing all defensive positions, Coaching and rules, Offensive and defensive strategy. Partial list of Big League tips on How to Play the Game: Tony Gwynn (hitting), Sammy Sosa (judging fly balls), Bernie Williams (playing the outfield), Mark Grace (approach to hitting), Alex Rodriguez (fielding ground balls), Jeff Bagwell (hitting), Roberto Alomar (fielding ground balls), Jaret Wright (pitching mechanics), Edgar Renteria (how to play SS), John Lackey (improving your pitching), Carlos Delgado (mastering 1B), Rocco Baldelli (basic approach at plate), Cristian Guzman (fielding ground balls), Danny Kolb (good approach on the mound), Dontrelle Willis (pitching strategies), Torii Hunter (playing the outfield), Jason Marquis (pitching with control), Chone Figgins (sliding), Orlando Cabrera (improving your game), Gary Bennett (becoming a better catcher), Ervin Santana (pitching under pressure), Mark Teixeira (playing 1B), Ryan Howard (hitting), Joey Gathright (playing the OF), Troy Tulowitzki (succeeding at the plate), Joel Zumaya (pitching with poise), Josh Johnson (pitching with confidence).
Foreword / Harold Reynolds -- Basic fundamentals, approaching the game -- Conditioning and drills, learning the basics of physical fitness -- Equipment, choosing the appropriate gear -- Practice, honing your skills -- Pitching: mechanics, learning different grips, types of pitches and deliveries -- Pitching: command, understanding how to best work the full strike zone -- Pitching: heat, developing a wind-up that adds velocity -- Hitting: approach, developing an effective batting stance -- Hitting: contact, evaluating footwork, arm extension and staying inside the ball -- Hitting: power, generating strength from your legs and driving the ball to all fields -- Coaching tips: fostering a winning attitude, handling umpires and utilizing video -- Advanced fundamentals: executing bunts, relays, double plays and the hit-and-run -- Baserunning: running through the bag, taking a lead, turning corners and sliding -- Fielding: catchers, handling pitchers, blocking balls in the dirt and framing -- Fielding: infielders, positioning yourself for ground balls, pop-ups and other plays -- Fielding: outfielders, approaching fly balls and bouncing balls, throwing and positioning yourself -- Rule book basics: examining some of baseball's rules -- Developing talent: helping players improve -- Drills: 40 ways to practice what you have learned.
"The official playing and coaching manual of Major League Baseball"--Cover.
Includes bibliographical references.
Keywords: Baseball